Endometriosis presenting as relapsing haemorrhagic ascites in a South Asian woman: a case report - Ahmed, Ushna; Chughtai, Novera (Journal of the Pakistan Medical Association, 2023)
Endometriosis presenting as ascites is a rare entity, and is more so in women of Asian ethnicity. Less than a hundred cases have been reported worldwide. Majority of patients present with abdominal distension and pain, draining massive blood stained serosanguineous fluid. This hinders future fertility prospects of these women. Ovarian suppression has been employed as a successful treatment, followed by definitive surgical treatment, such as bilateral salpingo-oophorectomy, to end the possibility of recurrences, which are otherwise always possible. We present the case of a woman of reproductive age, seeking fertility treatment, who had a more subtle presentation of moderate, but relapsing ascites of unknown origin in the past two years. Diagnostic laparoscopy and histopathology of the peritoneal deposits suggested endometriosis. Her ovarian function was suppressed, and she is currently underway of assisted reproduction for achieving a pregnancy. Keywords: Endometriosis, ascites, ovarian suppression.